Antidiarrheal and antispasmodic activities of Salvia officinalis are mediated through activation of K+ channels - Aslam Khan; Najeeb-; Khalid M. AlKharfy; Anwarul-Hassan Gilani (Bangladesh Pharmacological Society, 2011)
This study was conducted to provide pharmacological basis for the medicinal use of Salvia officinalis in diarrhea. The crude extract of S. officinalis was studied using the in vivo and in vitro assays.  The crude extract inhibited castor oil-induced diarrhea in mice at the dose of 100 and 300 mg/kg. In isolated rabbit jejunum, it caused a dose-dependent (0.1-3 mg/mL) relaxation of spontaneous as well as low K+ (25 mM) and high K+ (80 mM)-induced contractions, being distinctly more potent on low K+. Pretreatment of tissue with 4-aminopyridine (1 mM) almost completely blocked the inhibitory effect of crude extract on low K+.  These results indicate that the crude extract of S. officinalis possesses antidiarrheal and antispasmodic activities mediated possibly through the dominant activation of voltage-dependent K+ channels and this study provides sound pharmacological basis for its medicinal use in diarrhea and gut spasm.